Meaning And Function of Abstinence Expression in Segodorejo Society In Jombang East Java - Rani Jayanti (Universitas Negeri Surabaya, 2019)
Research which is focuses on meaning and function of abstinence expression in Segodorejo society in Jombang East Java. The aim of this research is explaining the meaning and function of abstinence expression in Segodorejo society in Jombang East Java. The theory of linguistic anthropology by Duranti (1997) and Jakobson (1980) is used in analysis study. Research categorizes as qualitative research, and the data is in form of meaning and functions. Technique analysis of data used in this research is improved by Miles and Huberman (1984), which is cover three steps, 1) data reduction, 2) data presentation, and 3) conclusion or verification. The result of this research shows that meaning of expression of Segodorejo society restriction in Jombang East Java includes: Prohibition of the Prohibition Educate, Time Challenge Religion Relates to Time, Precaution of Chastity, Abstinence of the Illness, Gross Abstinence, Declaration of Courtesy Challenge, Prohibition of Family Harmony, Abstinence of the Abstinence of Killing the Beast. Function of expression of Segodorejo society restriction in Jombang East Java includes: expressive function, conative function, referential function, fastest function, metalinguistic function.Keywords :.Function, linguistic anthropology, Jombang society